2017
DOI: 10.1177/1535370217697383
|View full text |Cite
|
Sign up to set email alerts
|

The soy-derived peptide Vglycin inhibits the growth of colon cancer cells in vitro and in vivo

Abstract: The antidiabetic properties and the capability of inducing differentiation of human colon adenocarcinoma cells of Vglycin have been reported in our previous studies. However, the anticancer potential of Vglycin on colon cancer cells and its possible related mechanisms were still unknown. In this study, we found that Vglycin could reduce growth, viability, and colony formation or colony size of CT-26, SW480, and NCL-H716 colon cancer cells. Moreover, Vglycin decreased tumor volume by 38% in xenograft mice trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
2
14
0
1
Order By: Relevance
“…The treatment of undifferentiated Caco2/TC7 cells with FPH exhibited a decrease in their viability, especially with PFPH that was correlated with incubation time. These results are in line with works reporting an anti-proliferative property of peptides and hydrolysates from soy [14], corn [12,31], chickpeas [13], and rice [11] on different cell models. Vglycin, a peptide isolated from soy, inhibited the proliferation of three types of colon cancer cells [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The treatment of undifferentiated Caco2/TC7 cells with FPH exhibited a decrease in their viability, especially with PFPH that was correlated with incubation time. These results are in line with works reporting an anti-proliferative property of peptides and hydrolysates from soy [14], corn [12,31], chickpeas [13], and rice [11] on different cell models. Vglycin, a peptide isolated from soy, inhibited the proliferation of three types of colon cancer cells [14].…”
Section: Discussionsupporting
confidence: 91%
“…However, Xue et al [13] reported that a chickpea-derived peptide inhibits the proliferation of breast cancer cells by increasing the p53 expression. Yet, Gao et al [14] found that peptides derived from soy Vglycin activate the expression levels of pro-apoptotic proteins and caspase-3.…”
Section: Introductionmentioning
confidence: 99%
“…* represents a significant difference between the untreated groups of both macrophage types (p < 0.05), and different letters in each group represent significantly different IL-10 production (p < 0.05). polypeptide isolated from pea seeds, took 24 h to cause a significant increase in apoptosis in the CT-26, SW480, and NCI-H716 colon cancer cell lines at 10 µM (Gao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Soy milk digestion extract (daizein, glycitein, genistein) might inhibit the proliferation of in vitro human prostate cancer cells by regulating the expression of ERβ, PSA, p21, Cyclin D1 and CDK4 in an estrogen receptor (ER)-dependent manner [ 49 ]. The soy-derived peptide Vglycin decreased the tumor volume by 38% in xenograft mice transplanted with colon cancer (CT-26) cells [ 50 ]. The mechanisms of these phenomena may be due to the down regulation of CDK2 and Cyclin D1, G1/S phase cell cycle arrest and the dysregulated expression of Bax, Bcl-2, and Mcl-1.…”
Section: Discussionmentioning
confidence: 99%